AIP Conference Proceedings: Preface - Schuh, Sonja; Drechsel, Horst; Heber, Ulrich (AIP Conference Proceedings, 2011)
CRIS-Team Scopus Importer:2020-12-21

Analysis of two eclipsing hot subdwarf binaries with a low mass stellar and a brown dwarf companion - Schaffenroth, Veronika; Geier, Stephan; Heber, Ulrich; Drechsel, Horst; Østensen, Roy H.; Maxted, Pierre F.L.; Kupfer, Thomas; Barlow, Brad N. (AIP Conference Proceedings, 2011)
The formation of hot subdwarf stars (sdBs), which are core helium-burning stars located on the extended horizontal branch, is still not understood. Many of the known hot subdwarf stars reside in close binary systems with short orbital periods between a few hours and a few days with either M star or white dwarf companions. Common envelope ejection is the most probable formation channel. Among these, eclipsing systems are of special importance because it is possible to constrain the parameters of both components tightly by combining spectroscopic and light curve analyses. We report the discovery of two eclipsing binaries with a brown dwarf (<0.07 M⊙) and a 0.15 M ⊙ late main sequence star companion in close orbits around sdB stars. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: brown dwarf; eclipsing binaries; HW Vir; sdB

A new bright eclipsing hot subdwarf binary from the ASAS and SuperWASP surveys - Schaffenroth, Veronika; Geier, Stephan; Drechsel, Horst; Heber, Ulrich; Wils, P.; Ostensen, R. H.; Maxted, P. F. L.; Di Scala, G. (Astronomy & Astrophysics, 2013)
We report the discovery of a bright (mV = 11.6 mag), eclipsing, hot subdwarf binary of spectral type B with a late main sequence companion from the All Sky Automated Survey (ASAS 102322-3737.0). Such systems are called HW Vir stars after the prototype. The lightcurve shows a grazing eclipse and a strong reflection effect. An orbital period of P = 0.13927 d, an inclination of i = 65.86, a mass ratio q = 0.34, a radial velocity semiamplitude K1 = 81.0 km s-1, and other parameters were derived from a combined spectroscopic and photometric analysis. The short period can only be explained by a common envelope origin of the system. The atmospheric parameters (T eff = 28 400 K, log g = 5.60) are consistent with a core helium-burning star located on the extreme horizontal branch. In agreement with that we derived the most likely sdB mass to be MsdB = 0.46 M ⊙, close to the canonical mass of such objects. The companion is a late M-dwarf with a mass of Mcomp = 0.16 M⊙. ASAS 102322-3737.0 is the third brightest of only 12 known HW Virginis systems, which makes it an ideal target for detailed spectroscopic studies and long-term photometric monitoring to search for period variations, e.g., those caused by a substellar companion. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Stars: early-type; Stars: fundamental parameters; Stars: individual: ASAS 102322-3737.0; Subdwarfs

A new HW Vir binary from the Palomar Transient Factory PTF1 J072455.75+125300.3: An eclipsing subdwarf B binary with a M-star companion - Schindewolf, Markus; Levitan, D.; Heber, Ulrich; Drechsel, Horst; Schaffenroth, Veronika; Kupfer, Thomas; Prince, T. (Astronomy & Astrophysics, 2015)
We report the discovery of an eclipsing binary - PTF1 J072456+125301- composed of a subdwarf B (sdB) star (g' = 17.2(m)) with a faint companion. Subdwarf B stars are core helium-burning stars, which can be found on the extreme horizontal branch. About half of them reside in close binary systems, but few are known to be eclipsing, for which fundamental stellar parameters can be derived. We conducted an analysis of photometric data and spectra from the Palomar 60 '' and the 200 '' Hale telescope, respectively. A quantitative spectral analysis found an effective temperature of T-eff = 33 900 +/- 350 K, log g = 5.74 +/- 0.08, and log(n(He)/n(H)) = -2.02 +/- 0.07, typical for an sdB star. The companion does not contribute to the optical light of the system, except through a distinct reflection effect. From the light curve an orbital period of 0.09980(25) d and a system inclination of 83.56 +/- 0.30 degrees were derived. The radial velocity curve yielded an orbital semi-amplitude of K-1 = 95.8 +/- 8.1 km s(-1). The mass for the M-type dwarf companion is 0.155 +/- 0.020 M-circle dot. PTF1 J072456+125301 has similar atmospheric parameters to those of pulsating sdB stars (V346 Hya stars). Therefore it could be a high-priority object for asteroseismology, if pulsations were detected such as in the enigmatic case of NY Vir.
Keywords: binaries: eclipsing; stars: early-type; stars: evolution; stars: fundamental parameters; stars: horizontal-branch; subdwarfs

Binaries discovered by the MUCHFUSS project: SDSS J08205+0008 - An eclipsing subdwarf B binary with a brown dwarf companion - Geier, Stephan; Schaffenroth, Veronika; Drechsel, Horst; Heber, Ulrich; Kupfer, Thomas; Tillich, A.; Ostensen, R. H.; Smolders, K.; Degroote, P.; Maxted, P. F. L.; Barlow, B. N.; Gaensicke, B. T.; et al. (Astrophysical Journal Letters, 2011)
Hot subdwarf B stars (sdBs) are extreme horizontal branch stars believed to originate from close binary evolution. Indeed about half of the known sdB stars are found in close binaries with periods ranging from a few hours to a few days. The enormous mass loss required to remove the hydrogen envelope of the red-giant progenitor almost entirely can be explained by common envelope ejection. A rare subclass of these binaries are the eclipsing HW Vir binaries where the sdB is orbited by a dwarf M star. Here, we report the discovery of an HW Vir system in the course of the MUCHFUSS project. A most likely substellar object (≃0.068 M⊙) was found to orbit the hot subdwarf J08205+0008 with a period of 0.096 days. Since the eclipses are total, the system parameters are very well constrained. J08205+0008 has the lowest unambiguously measured companion mass yet found in a subdwarf B binary. This implies that the most likely substellar companion has not only survived the engulfment by the red-giant envelope, but also triggered its ejection and enabled the sdB star to form. The system provides evidence that brown dwarfs may indeed be able to significantly affect late stellar evolution. © 2011. The American Astronomical Society. All rights reserved.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: spectroscopic; brown dwarfs; stars: horizontal-branch; stars: individual

EPIC 216747137: A new HW Vir eclipsing binary with a massive sdOB primary and a low-mass M-dwarf companion - Silvotti, R.; Schaffenroth; Heber, Ulrich; Ostensen, R. H.; Telting, J. H.; Vos, J.; Kilkenny, D.; Mancini, L.; Ciceri, S.; Irrgang, Andreas; Drechsel, Horst (Monthly Notices of the Royal Astronomical Society, 2021)
EPIC 216747137 is a new HW Virginis system discovered by the Kepler spacecraft during its K2 'second life'. Like the other HW Vir systems, EPIC 216747137 is a post-common-envelope eclipsing binary consisting of a hot subluminous star and a cool low-mass companion. The short orbital period of 3.87 h produces a strong reflection effect from the secondary (∼9 per cent in the R band). Together with AA Dor and V1828 Aql, EPIC 216747137 belongs to a small subgroup of HW Vir systems with a hot evolved sdOB primary. We find the following atmospheric parameters for the hot component: Teff = 40400 ± 1000 K, log g = 5.56 ± 0.06, and log(N(He)/N(H)) =-2.59 ± 0.05. The sdOB rotational velocity v sin i = 51 ± 10 km s-1 implies that the stellar rotation is slower than the orbital revolution and the system is not synchronized. When we combine photometric and spectroscopic results with the Gaia parallax, the best solution for the system corresponds to a primary with a mass of about 0.62 M close to, and likely beyond, the central helium exhaustion, while the cool M-dwarf companion has a mass of about 0.11 M.
CRIS-Team Scopus Importer:2021-02-05
Keywords: binaries: eclipsing; stars: horizontal branch; stars: individual: EPIC 216747137

Improved physical properties of the quadruple sub-system with the eclipsing binary QZ Carinae - Mayer, P.; Harmanec, P.; Zasche, P.; Catalan-Hurtado, R.; Barlow, B. N.; Fremat, Y.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Christie, G. W.; Walker, W. S. G.; et al. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
Using a collection of 79 spectra of the quadruple system QZ Car, we were able - for the first time in the optical region - to measure radial velocities of both components of the eclipsing subsystem Ac, and in combination with the photometric solution to obtain masses and radii of both bodies. We confirm that the Ac binary is a semi-detached system with a brighter primary Ac1 and a more massive secondary Ac2. Variations due to the light-time effect and secular changes in the systemic velocities of both binaries, Aa and Ac, allowed us to estimate the period of mutual orbit of binaries Aa and Ac to be about 11700 d. Preliminary improved basic properties of the system and its components are provided.
CRIS-Team WoS Importer:2020-04-21

MUCHFUSS - Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS - Geier, Stephan; Schaffenroth, Veronika; Hirsch, H.; Tillich, A.; Heber, Ulrich; Maxted, P. F. L.; Ostensen, R. H.; Barlow, B. N.; O'Toole, S. J.; Kupfer, Thomas; Marsh, T.; Gaensicke, Boris T; et al. (Astronomische Nachrichten, 2012)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions (white dwarfs with masses M > 1.0 M ⊙, neutron stars or black holes). The existence of such systems is predicted by binary evolution calculations and some candidate systems have been found. We identified ≃1100 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS). Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. About 70 radial velocity variable subdwarfs have been selected as good candidates for follow-up time resolved spectroscopy to derive orbital parameters and photometric follow-up to search for features like eclipses in the light curves. Up to now we found nine close binary sdBs with short orbital periods ranging from ≃0.07 d to 1.5 d. Two of them are eclipsing binaries with companions that are most likely of substellar nature © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

Spectroscopic and photometric analysis of the HW Vir star PTF1 J011339.09+225739.1 - Woltz, Maximilian; Kupfer, Thomas; Drechsel, Horst; Heber, Ulrich; Irrgang, Andreas; Hermes, J. J.; Bloemen, Steven; Levitan, D.; Dhillon, Vik S.; Marsh, Thomas (DE GRUYTER POLAND SP ZOO, 2018)
HW Vir systems are rare eclipsing binary systems including a subdwarf B star (sdB) with a faint companion, mostly M-dwarfs. Up to now, 19 HW Vir systems have been published, three of them with substellar companions. We report the spectroscopic as well as photometric observation of the eclipsing sdB binary PTF1 J011339.09+225739.1 (PTF1 J0113) in a close (a=0.722 +/- 0.023 R-circle dot), short period (P = 0.0933731(3)d) orbit. A quantitative spectral analysis of the sdB yields T-eff =29280 +/- 720 K, log(g)=5.77 +/- 0.09 dex, and log(y)=-2.32 +/- 0.12. The circular orbital velocity of the sdB of K-1 =74.2 +/- 1.7 km s(-1) is derived from the radial velocity curve. Except for the strong reflection effect, no other light contribution of the companion could be detected. The light curves - recorded with ULTRACAM - were analyzed using the Wilson-Devinney code. We find an inclination angle of i=79.88 +/- 0.18 degrees. Because our first attempts to determine q failed, we calculated large grids of synthetic lightcurves for several mass ratios. Because of degeneracy, good solutions for different mass ratios were found - the one at q = 0.24 is consistent with the sdB's canonical mass (M-sdB = 0.47 M-circle dot). Accordingly, the mass of the companion is M-2=0.112 +/- 0.003 M-circle dot. The radii of the two components were also derived: R-sdB=0.178 +/- 0.006 R-circle dot and R-2 = 0.158 +/- 0.009 R-circle dot. Thus, the results for the secondary are consistent with an M-dwarf as secondary.
Keywords: subdwarfs; binaries: eclipsing; stars: early-type; stars: evolution; stars: fundamental parameters; stars: horizontal-branch

The EREBOS project: Investigating the effect of substellar and low-mass stellar companions on late stellar evolution Survey, target selection, and atmospheric parameters - Schaffenroth, V.; Barlow, B. N.; Geier, S.; Vuckovic, M.; Kilkenny, D.; Wolz, Maximilian; Kupfer, T.; Heber, Ulrich; Drechsel, Horst; Kimeswenger, S.; Marsh, T.; Wolf, M.; et al. (Astronomy & Astrophysics, 2019)
Eclipsing post-common-envelope binaries are highly important for resolving the poorly understood, very short-lived common-envelope phase of stellar evolution. Most hot subdwarfs (sdO/Bs) are the bare helium-burning cores of red giants that have lost almost all of their hydrogen envelope. This mass loss is often triggered by common-envelope interactions with close stellar or even substellar companions. Cool companions to hot subdwarf stars such as late-type stars and brown dwarfs are detectable from characteristic light-curve variations - reflection effects and often eclipses. In the recently published catalog of eclipsing binaries in the Galactic Bulge and in the Asteroid Terrestrial-impact Last Alert System (ATLAS) survey, we discovered 125 new eclipsing systems showing a reflection effect seen by visual inspection of the light curves and using a machine-learning algorithm, in addition to the 36 systems previously discovered by the Optical Gravitational Lesing Experiment (OGLE) team. The Eclipsing Reflection Effect Binaries from Optical Surveys (EREBOS) project aims at analyzing all newly discovered eclipsing binaries of the HW Vir type (hot subdwarf + close, cool companion) based on a spectroscopic and photometric follow up to derive the mass distribution of the companions, constrain the fraction of substellar companions, and determine the minimum mass needed to strip off the red-giant envelope. To constrain the nature of the primary we derived the absolute magnitude and the reduced proper motion of all our targets with the help of the parallaxes and proper motions measured by the Gaia mission and compared those to the Gaia white-dwarf candidate catalog. It was possible to derive the nature of a subset of our targets, for which observed spectra are available, by measuring the atmospheric parameter of the primary, confirming that less than 10% of our systems are not sdO/Bs with cool companions but are white dwarfs or central stars of planetary nebula. This large sample of eclipsing hot subdwarfs with cool companions allowed us to derive a significant period distribution for hot subdwarfs with cool companions for the first time showing that the period distribution is much broader than previously thought and is ideally suited to finding the lowest-mass companions to hot subdwarf stars. The comparison with related binary populations shows that the period distribution of HW Vir systems is very similar to WD+dM systems and central stars of planetary nebula with cool companions. In the future, several new photometric surveys will be carried out, which will further increase the sample of this project, providing the potential to test many aspects of common-envelope theory and binary evolution.
CRIS-Team WoS Importer:2019-10-11

The ESO supernovae type Ia progenitor survey (SPY) The radial velocities of 643 DA white dwarfs - Napiwotzki, R.; Karl, C. A.; Lisker, T.; Catalan, S.; Drechsel, Horst; Heber, Ulrich; Homeier, D.; Koester, D.; Leibundgut, B.; Marsh, T. R.; Moehler, S.; Nelemans, G.; et al. (Astronomy & Astrophysics, 2020)
Close double degenerate binaries are one of the favoured progenitor channels for type Ia supernovae, but it is unclear how many suitable systems there are in the Galaxy. We report results of a large radial velocity survey for double degenerate (DD) binaries using the UVES spectrograph at the ESO VLT (ESO SN Ia Progenitor surveY - SPY). Exposures taken at different epochs are checked for radial velocity shifts indicating close binary systems. We observed 689 targets classified as DA white dwarfs (displaying hydrogen-rich atmospheres), of which 46 were found to possess a cool companion. We measured radial velocities (RV) of the remaining 643 DA white dwarfs. We managed to secure observations at two or more epochs for 625 targets, supplemented by eleven objects meeting our selection criteria from literature. The data reduction and analysis methods applied to the survey data are described in detail. The sample contains 39 double degenerate binaries, only four of which were previously known. Twenty are double-lined systems, in which features from both components are visible, the other 19 are single-lined binaries. We provide absolute RVs transformed to the heliocentric system suitable for kinematic studies. Our sample is large enough to sub-divide by mass: 16 out of 44 low mass targets (<= 0.45 M-circle dot) are detected as DDs, while just 23 of the remaining 567 targets with multiple spectra and mass > 0.45 M-circle dot are double. The detected fraction amongst the low mass objects (36.4 +/- 7.3%) is significantly higher than for the higher-mass, carbon-oxygen core dominated part of the sample (3.9 +/- 0.8%), but it is much lower than expected from the detection efficiency for companion masses of 0.05 M-circle dot or higher and a 100% binary fraction. This suggests either companion stars of with a mass below 0.05 M-circle dot or some of the low mass white dwarfs are single.
Keywords: techniques: radial velocities; binaries: close; binaries: spectroscopic; supernovae: general; white dwarfs

The ESO supernovae type Ia progenitor survey (SPY): The radial velocities of 643 DA white dwarfs - Napiwotzki, R.; Karl, C. A.; Lisker, T.; Catalan, S.; Drechsel, Horst; Heber, Ulrich; Homeier, D.; Koester, D.; Leibundgut, B.; Marsh, T. R.; Moehler, S.; Nelemans, G.; et al. (Astronomy & Astrophysics, 2020)
Close double degenerate binaries are one of the favoured progenitor channels for type Ia supernovae, but it is unclear how many suitable systems there are in the Galaxy. We report results of a large radial velocity survey for double degenerate (DD) binaries using the UVES spectrograph at the ESO VLT (ESO SN Ia Progenitor surveY - SPY). Exposures taken at different epochs are checked for radial velocity shifts indicating close binary systems. We observed 689 targets classified as DA white dwarfs (displaying hydrogen-rich atmospheres), of which 46 were found to possess a cool companion. We measured radial velocities (RV) of the remaining 643 DA white dwarfs. We managed to secure observations at two or more epochs for 625 targets, supplemented by eleven objects meeting our selection criteria from literature. The data reduction and analysis methods applied to the survey data are described in detail. The sample contains 39 double degenerate binaries, only four of which were previously known. Twenty are double-lined systems, in which features from both components are visible, the other 19 are single-lined binaries. We provide absolute RVs transformed to the heliocentric system suitable for kinematic studies. Our sample is large enough to sub-divide by mass: 16 out of 44 low mass targets (<= 0.45 M-circle dot) are detected as DDs, while just 23 of the remaining 567 targets with multiple spectra and mass > 0.45 M-circle dot are double. The detected fraction amongst the low mass objects (36.4 +/- 7.3%) is significantly higher than for the higher-mass, carbon-oxygen core dominated part of the sample (3.9 +/- 0.8%), but it is much lower than expected from the detection efficiency for companion masses of 0.05 M-circle dot or higher and a 100% binary fraction. This suggests either companion stars of with a mass below 0.05 M-circle dot or some of the low mass white dwarfs are single.
CRIS-Team WoS Importer:2020-07-24
Keywords: techniques: radial velocities; binaries: close; binaries: spectroscopic; supernovae: general; white dwarfs

Towards a consistent model of the hot quadruple system HD 93206=QZ Carinae - Mayer, P.; Harmanec, P.; Zasche, P.; Broz, M.; Catalan-Hurtado, R.; Barlow, B. N.; Frondorf, W.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Pigulski, A.; et al. (Astronomy & Astrophysics, 2022)
The hot nine-component system HD 93206, which contains a gravitationally bounded eclipsing Ac1+Ac2 binary (P=5:9987 d) and a spectroscopic Aa1+Aa2 (P=20 :734 d) binary can provide important insights into the origin and evolution of massive stars. Using archival and new spectra, and a rich collection of ground-based and space photometric observations, we carried out a detailed study of this object. We provide a much improved description of both short orbits and a good estimate of the mutual period of both binaries of about 14 500 d (i.e. 40 years). For the first time, we detected weak lines of the fainter component of the 6.0 d eclipsing binary in the optical region of the spectrum, measured their radial velocities, and derived a mass ratio of M-Ac2/M-Ac1 = 1 :29, which is the opposite of what was estimated from the International Ultraviolet explorer (IUE) spectra. We confirm that the eclipsing subsystem Ac is semidetached and is therefore in a phase of large-scale mass transfer between its components. The Roche-lobe filling and spectroscopically brighter component Ac1 is the less massive of the two and is eclipsed in the secondary minimum. We show that the bulk of the H alpha emission, so far believed to be associated with the eclipsing system, moves with the primary O9.7 I component Aa1 of the 20.73 d spectroscopic binary. However, the weak emission in the higher Balmer lines seems to be associated with the accretion disc around component Ac2. We demonstrate that accurate masses and other basic physical properties including the distance of this unique system can be obtained but require a more sophisticated modelling. A first step in this direction is presented in the accompanying Paper II (Broz et al.).
CRIS-Team WoS Importer:2022-11-04

Towards a consistent model of the hot quadruple system HD 93206=QZ Carin ae II. N-body model - Broz, M.; Harmanec, P.; Zasche, P.; Catalan-Hurtado, R.; Barlow, B. N.; Frondorf, W.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Labadie-Bartz, J.; Christie, G. W.; et al. (Astronomy & Astrophysics, 2022)
Aims. HD 93206 is a massive early-type stellar system composed of components resolved by direct imaging (Ab, Ad, B, C, D) and a compact subsystem (Aa1, Aa2, Ac1, Ac2). Its geometry was already determined on the basis of extensive photometric, spectroscopic, and interferometric observations. However, the fundamental absolute parameters are still not known precisely enough.
CRIS-Team WoS Importer:2022-11-04